02.11 Il-38 is not involved in the modulation of imq-induced skin inflammation. (1st March 2017) - Palomo, Jennifer; Troccaz, Sabina; Rodriguez, Emiliana; Talabot-Ayer, Dominique; Gabay, Cem; Palmer, Gaby
Abstract : Background: Psoriasis is a common chronic skin disorder caused by a dysregulated crosstalk between immune and resident cells (eg, keratinocytes). The identification of the pathogenic role of several cytokines in psoriasis led to the development of successful therapies. Recently, IL-36 cytokines, which belong to the IL-1 family, were shown to be involved in the pathogenesis of psoriasis. Mice deficient in IL-36 receptor (IL-36R) were protected from imiquimod (IMQ)-induced skin inflammation, whereas IL-36R antagonist (IL-36Ra) KO mice exhibited a more severe phenotype. The objective of our study was to examine the expression and function of IL-38, a newly discovered IL-1 family member with supposed IL-36 inhibitory properties, in the IMQ model of psoriasis. Materials and methods: IL-38 mRNA expression was determined in skin samples, at steady state or after IMQ application. IL-38 KO or IL-36Ra KO mice and their respective WT littermates were challenged with the topical application of IMQ on the left ear during 7 days. The severity of skin inflammation was assessed by daily measurement of ear thickness using a calliper, by semi-quantitative histologic scoring, and by measuring mRNA levels of inflammatory markers. Results: At the peak of IMQ-induced skin inflammation, IL-38 mRNA levels were lower than in normal skin, whereas IL-36Ra mRNA levels were increased in IMQ treated skin. The severity of skin inflammation, as assessed by ear thickness, histological changes (leukocyte infiltration and epidermis hyperplasia) and pro-inflammatory mediator transcript levels, was not significantly different in IL-38 KO and WT mice. After cessation of topical IMQ application, the resolution of skin inflammation was also not altered by IL-38 deficiency. As opposed to these findings, IL-36Ra deficient mice displayed more severe pathological changes as compared to WT mice. Conclusions: We showed that endogenous IL-38 is not involved in the development and the resolution of IMQ-induced skin inflammation. Our findings suggest that IL-38 does not exert IL-36 inhibitory activities in the skin.